Fully Transparent Friction‐Modulation Haptic Device Based on Piezoelectric Thin Film. (2nd July 2020) - Glinsek, Sebastjan; Mahjoub, Mohamed Aymen; Rupin, Matthieu; Schenk, Tony; Godard, Nicolas; Girod, Stéphanie; Chemin, Jean‐Baptiste; Leturcq, Renaud; Valle, Nathalie; Klein, Sébastien; Chappaz, Cédrick; Defay, Emmanuel
Abstract: Standing Lamb waves in vibrating plates enable haptic interfaces. If the out‐of‐plane displacement of these waves exceeds 1 µm at frequencies above 25 kHz, a silent friction modulation can be created between a human finger and a vibrating plate. A fully transparent friction‐modulation haptic device based on a piezoelectric thin film is demonstrated. The antisymmetric Lamb mode induced at 73 kHz allows for a functional performance that fulfills all conditions for practical use. Out‐of‐plane displacement reaches 2.9 µm when 150 V unipolar voltage is applied. The average transmittance of the whole transducer reaches 75%. The key points of this technology are: 1) a thin HfO2 layer between lead zirconate titanate film and substrate that prevents chemical reaction between them; 2) the efficient integration of transparent indium tin oxide electrodes and solution‐derived piezoelectric lead zirconate titanate thin film onto optical‐grade fused silica; and 3) the use of a transparent insulating layer made of SU‐8 photoresist. Abstract : A transparent friction‐modulation haptic device is demonstrated. The stack consists of a fused silica substrate, HfO2 barrier, Pb(Zr, Ti)O3 piezoelectric film, transparent interdigitated indium tin oxide electrodes, and SU‐8 insulating layer. The antisymmetric Lamb mode at 73 kHz allows for a silent functional performance that fulfills conditions for practical use, that is, displacement >1 µm at 60 V.